A transformação de Darboux-Bianchi para superfícies isotérmicas em R³ - Canevari, Samuel da Cruz (2004)
In this work we develop the transformation theory for isothermic surfaces in Euclidean space IR3 due to Darboux and Bianchi. As a consequence, we describe a method for constructing new solutions of the nonlinear system of partial diferential equations associated to an isothermic surface in IR3 starting from a given one.